2006
DOI: 10.1080/01902140600817481
|View full text |Cite
|
Sign up to set email alerts
|

TISSUE INHIBITOR OF METALLOPROTEINASE-3 IS UP-REGULATED BY TRANSFORMING GROWTH FACTOR-β1 IN VITRO AND EXPRESSED IN FIBROBLASTIC FOCI IN VIVO IN IDIOPATHIC PULMONARY FIBROSIS

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by fibroblast expansion and extracellular matrix accumulation. However, the mechanisms involved in matrix remodeling have not been elucidated. In this study, the authors aimed to evaluate the expression of the tissue inhibitors of matrix metalloproteinases (TIMPs) in human fibroblasts and whole tissues from IPF and normal lungs. They also determined the role of mitogen-activated protein kinase (MAPK) in TIMP3 expression. TIMP1, TIMP2, and TIMP3 were highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Interestingly, tissue inhibitor of metalloproteinase (TIMP)-3, an inhibitor of MMPs, was upregulated by 3.6-to 8.8-fold. TIMP3 is believed to be an inhibitor of tumor progression; however, it has also been shown to be a key factor in pathologic fibrosis (42). Several extracellular matrix structural components related to myofibroblast differentiation were also up-regulated by TGFh such as collagens, elastin, fibronectin, and matrix Gla protein (MGP).…”
Section: Cancer Researchmentioning
confidence: 99%
“…Interestingly, tissue inhibitor of metalloproteinase (TIMP)-3, an inhibitor of MMPs, was upregulated by 3.6-to 8.8-fold. TIMP3 is believed to be an inhibitor of tumor progression; however, it has also been shown to be a key factor in pathologic fibrosis (42). Several extracellular matrix structural components related to myofibroblast differentiation were also up-regulated by TGFh such as collagens, elastin, fibronectin, and matrix Gla protein (MGP).…”
Section: Cancer Researchmentioning
confidence: 99%
“…It is believed that TIMP/MMP imbalance is a determinant of fibrogenesis [134][135][136][137]. For example, TIMP1 was upregulated in a mouse model of bleomycin-induced pulmonary fibrosis [138] and TIMP3 was upregulated in patients with IPF [139]. Upregulation of TIMP1 or TIMP3 generates a ''noncollagenolytic microenvironment'' and leads to excessive deposition of extracellular matrix [137].…”
Section: Dysregulation Of Mmps In Different Lung Disorders and Its Thmentioning
confidence: 99%
“…On the other hand, several pathologies involving fibrosis show an increase in MMP expression, including gelatinase A. Augmented expression of MMP-2 was found in submucous (29), skin (30), liver (31), and lung fibrosis (32,33) and dystrophic myotubes from fibrotic muscles of Duchenne muscular dystrophy (34). It has been shown that transforming growth factor type ␤ induces an increase in the amount of MMP-2 in fibroblasts (35) and that CTGF induces MMP-2 expression in cultured renal interstitial fibroblasts (36).…”
mentioning
confidence: 99%